SOURCES OF INDIVIDUAL DIFFERENCES IN EDUCATION - Septiara, Sabgi Wulan; Daffah, Vhaliesca; Magdalena, Ina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2021)
Individual differences that need to be considered in the implementation of classroom teaching are factors related to the readiness of children to receive teaching because these differences will determine the education system as a whole. These differences with other individual approach as well, but it is still realized that education is not solely aimed at developing individuals as individuals, but also in relation to the varied patterns of community life. The factors that influence individual differences are self-concept, the anxiety experienced by students, learning motivation.